2016
DOI: 10.1002/jso.24231
|View full text |Cite
|
Sign up to set email alerts
|

Axillary reverse mapping in patients with breast cancer: Is it oncologically safe?

Abstract: There is a high risk of ARM node involvement, approximately a quarter, in patients with preoperatively known lymph node metastases from breast cancer. However, it may be safe to preserve a clinically non-suspicious ARM node in patients with a positive SLNB who require a completion ALND. J. Surg. Oncol. 2016;113:726-731. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
7
15
0
Order By: Relevance
“…Twenty-nine articles published between January 2007 and January 2020 describing studies of 4954 patients were included in this meta-analysis [ 1 , 2 , [6] , [7] , [8] , [9] , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. These included four randomized controlled trials [ 1 , [20] , [21] , [22] ] and 25 prospective non-randomized studies [ 2 , [6] , [7] , [8] , [9] , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [23] , [24] , [25] ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-nine articles published between January 2007 and January 2020 describing studies of 4954 patients were included in this meta-analysis [ 1 , 2 , [6] , [7] , [8] , [9] , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. These included four randomized controlled trials [ 1 , [20] , [21] , [22] ] and 25 prospective non-randomized studies [ 2 , [6] , [7] , [8] , [9] , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [23] , [24] , [25] ].…”
Section: Resultsmentioning
confidence: 99%
“…(2016) [ 33 ] Prospective India ALND alone (50) Radioisotope ALND: 94%(47/50) NA 11%(5/47) NA NA Moderate quality 04/2012–08/2012 Ngui et al. (2016) [ 26 ] Prospective Australia ALND alone (87) Blue dye ALND: 77%(67/87) 9%(3/32) 27%(18/67) NA NA Moderate quality 06/2012–12/2014 Noguchi et al. (2016) [ 2 ] Prospective Japan SLNB with or without ALND(292); ALND with SLNB (48) Blue dye + fluorescence SLND: 31% (90/292) ALND: 86%(36/42) 27%(77/286) 21%(19/90) SLNB: 1%(2/244) 45 months Moderate quality 06/2012–12/2014 Nos et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we found only a few studies had described the distribution pattern of SLNs in axillary tissues. [ 22 24 ] For example, Clough et al [ 25 ] explored the distribution of SLNs in axillary tissues in 242 breast cancer patients, using blue dye or radioisotope to trace the SLNs. They found that the majority of SLNs were located at the medial part of the axilla, alongside the lateral thoracic vein.…”
Section: Discussionmentioning
confidence: 99%